Management Pattern of Facilities and Infrastructure in Improving Learning Quality in SMP Negeri 1 Hamparan Perak - Nuzurul Harmuliani; Rubino Rubino (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to determine the planning of facilities and infrastructure in improving the quality of learning, to determine the procurement of facilities and infrastructure in improving the quality of learning, to determine the use or utilization of facilities and infrastructure in improving the quality of learning and to determine the maintenance of facilities and infrastructure in improving the quality of learning. This research uses qualitative research methods using a naturalistic approach in which data sources are obtained based on a natural situation as it is. Data collection procedures using observation, interviews and documentation studies. Then the data analysis technique uses (a) data reduction, (b) data presentation, and (c) conclusion. The results of the study found that: 1) Planning facilities and infrastructure based on needs analysis as well as proposals from teachers or other staff and determining the priority scale according to the availability of funds and the level of importance of facilities and infrastructure. 2) Procurement of facilities and infrastructure by purchasing from available funds or budgets that have been set. 3) The use of facilities and infrastructure has rules and schedules that have been available. 4) Maintenance of facilities and infrastructure is carried out by all school residents both special officers, principals, teachers, and other students are responsible for maintaining and maintaining the facilities and infrastructure available. 5) Supervision of facilities and infrastructure is directly responsible for the deputy head of facilities and infrastructure. Facilities and infrastructure management is a very important component in efforts to improve the quality of learning in schools. In order to improve the quality of learning in schools, of course, it is necessary to pay attention to how to manage good facilities and infrastructure, so that learning objectives can be achieved effectively and efficiently. Keywords: Facilities and Infrastructure Management, Learning Quality